Joint bandwidth and power allocation algorithm in cognitive radio network with consideration of utility and fairness - Ji-lei YAN; Jian-dong LI; Lin-jing ZHAO; Quan DONG (Tongxin xuebao)
A unified utility function was designed to adapt to different types of services and an optimization problem was formulated based on the network utility maximization model.By applying the Lagrange duality method,a distributed joint bandwidth and power allocation algorithm was proposed.Simulation results show that this algorithm can effectively allocate proper resources to various types of secondary users.It can not only maximize the total utility of all secondary users but also maintain the utility fairness among them.